New Record of Kalidasa Lanata (Drury, 1773) From Ailanthus Triphysa in Kerala, India - R, Deepakkumar (Indian Journal of Hill Farming, 2018)
Ailanthus triphysa is a multipurpose tree which is affected by the number of pests. The sap sucking bug called Kalidasa lanata (Drury, 1773) is newly recorded from Ailanthus triphysa (Dennst.) Alston. It was belonging to the order Hemiptera and family Fulgoridae.Adult body length 38Â±3mm. Tegmina of bug was pale greenish-testaceous in colour with numerous black spots and one third of tegmina tip is ashy coloured band with small numerous black spots. Abdomen is red in colour. This paper presents detailed taxonomiccharacters of the species and a list of species reported in the family Fulgoridae from Kerala.